Rapid preparation process, structure and thermal stability of lanthanum doped alumina aerogels with a high specific surface area. Issue 31 (10th March 2016) - Yang, Jingfeng; Wang, Qihua; Wang, Tingmei; Liang, Yongmin
Abstract : In this study, we developed a new and rapid preparation method of alumina aerogels based on the sol–gel method and supercritical drying technique and prepared alumina aerogels with high specific surface area. Abstract : In this study, we developed a new and rapid preparation method of alumina aerogels based on the sol–gel method and supercritical drying technique. In the developed method, the prepared wet gels were sealed to directly conduct supercritical drying without aging or solvent exchange which is required in conventional supercritical drying and ambient pressure drying techniques, which greatly shortened the preparation process. Lanthanum doped alumina aerogels with a high specific surface area (SSA) were prepared firstly according to the developed method and then its structure and thermal stability at high temperature were investigated. Investigation results proved that the incorporation of lanthanum resulted in the formation of LaAl11 O18 on the surface of alumina particles, which distinctly delayed the transformation of the α-phase, and improved the thermal stability. Under the optimum atomic ratio of La/Al = 0.05, lanthanum doped alumina aerogels possessed high SSA and pore volume, while excessive lanthanum would result in the decreases in SSA and pore volume. Lanthanum doped alumina aerogels still had a high SSA and pore volume at 1000 °C and was not transformed into α-phase until the temperature rose to 1300 °C, exhibiting the excellent thermal stability. However, its SSA drastically decreased due to the collapse of pore structure.